Karakteristik Laju Regangan Melar pada Baja Tahan Karat Austenitic 316L - Ekaputra, I. M. W.; Haryadi, Gunawan Dwi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2017)
In this study, the creep strain rate characteristics of austenitic 316L stainless steel was investigated from the uniaxial creep-rupture test. The tests were conducted under various applied load levels with a constant temperature at 525oC. The creep exponent was obtained by applying a Norton’s law equation on a regression line of creep strain rate vs. stress curve. The steel clearly showed an instantaneous primary stage, following with the secondary and tertiary stages on the creep curve. It was found that the creep rupture time decreased systematically with an increase in the stress. The secondary stage of creep curve almost dominated the creep’s lifetime. Therefore, the creep strain rate was determined from the minimum strain rate on this stage. The obtained creep exponent indicated that the responsible creep mechanism was grain boundary sliding or diffusional creep mechanism